On dendrograms, ordinations and functional spaces: methodological choices or pitfalls? - Marcus V. Cianciaruso; Fernando Sobral; Alexander Lees (Frontiers of Biogeography)
A number of concerns persist regarding (i) how functional spaces should be quantified, (ii) how phylogenetic richness should be calculated, (iii) and how functional beta diversity should be calculated. Because all current methods have their shortcomings we think that analytical choices are as much a matter of knowing the limitations of the data and knowing the working hypothesis. Only then can one follow their personal choice, weighing up the shortcomings of different methods that, at the end of the day, usually produce qualitatively similar results.